Microstructural observations of an AA6082-T6 Hybrid Metal Extrusion & Bonding (HYB) butt weld. (June 2022) - Salvati, Enrico; Lanzutti, Alex; Magnan, Michele; Sandnes, Lise; Berto, Filippo; Grong, Øystein
Abstract: Hybrid Metal Extrusion & Bonding (HYB) is a relatively new solid-state welding method that distinguishes from the more traditional ones by utilising filler material addition to obtain joining. Regarding the mechanical properties, previous research has shown that HYB has the capability to outperform comparable fusion welds and match that of comparable Frictions Stir Welds. The present work is concerned with the microstructural characterisation of a 4 mm thick AA6082-T6 HYB butt weld, with main emphasis on the region of the joint Thermo-Mechanical Affected Base Material (TMA-BM). A sample extracted from the joint was examined using different experimental techniques, including optical microscopy, EBSD, EDX and hardness measurements. The formation of sharp interfaces or porosity between the base and the filler material was observed and interpreted. Grain refinements of the base material were witnessed and the main causes of this phenomenon were discussed, along with softening behaviour experienced in the TMA-BM of the weld. The implications of this work are relevant as they unveil important microstructural aspects that characterise this type of joint, as well as provide important directions for future research investigations. Graphical Abstract: ga1